Towards Improved Prognostic Scores Predicting Survival in Patients with Brain Metastases: A Pilot Study of Serum Lactate Dehydrogenase Levels. (19th April 2012) - Nieder, Carsten; Marienhagen, Kirsten; Dalhaug, Astrid; Norum, Jan
Abstract : Accurate prognostic information is desirable when counselling patients with brain metastases regarding their therapeutic options and life expectancy. Based on previous studies, we selected serum lactate dehydrogenase (LDH) as a promising factor on which we perform a pilot study investigating methodological aspects of biomarker studies in patients with brain metastases, before embarking on large-scale studies that will look at a larger number of candidate markers in an expanded patient cohort. For this retrospective analysis, 100 patients with available information on LDH treated with palliative whole-brain radiotherapy were selected. A comprehensive evaluation of different LDH-based variables was performed in uni- and multivariate tests. Probably, the most intriguing finding was that LDH kinetics might be more important, or at least complement, information obtained from a single measurement immediately before radiotherapy. LDH and performance status outperformed several other variables that are part of prognostic models such as recursive partitioning analyses classes and graded prognostic assessment score. LDH kinetics might reflect disease behaviour in extracranial metastatic and primary sites without need for comprehensive imaging studies and is a quite inexpensive diagnostic test. Based on these encouraging results, confirmatory studies in a larger cohort of patients are warranted.